Triclustering Implementation Using Hybrid δ-Trimax Particle Swarm Optimization and Gene Ontology Analysis on Three-Dimensional Gene Expression Data - Titin Siswantining; Maria Armelia Sekar Istianingrum; Saskya Mary Soemartojo; Devvi Sarwinda; Noval Saputra; Setia Pramana; Rully Charitas Indra Prahmana (Mathematics, 2023)
Triclustering is a data mining method for grouping data based on similar characteristics. The main purpose of a triclustering analysis is to obtain an optimal tricluster, which has a minimum mean square residue (MSR) and a maximum tricluster volume. The triclustering method has been developed using many approaches, such as an optimization method. In this study, hybrid <semantics>δ</semantics>-Trimax particle swarm optimization was proposed for use in a triclustering analysis. In general, hybrid <semantics>δ</semantics>-Trimax PSO consist of two phases: initialization of the population using a node deletion algorithm in the <semantics>δ</semantics>-Trimax method and optimization of the tricluster using the binary PSO method. This method, when implemented on three-dimensional gene expression data, proved useful as a Motexafin gadolinium (MGd) treatment for plateau phase lung cancer cells. For its implementation, a tricluster that potentially consisted of a group of genes with high specific response to MGd was obtained. This type of tricluster can then serve as a guideline for further research related to the development of MGd drugs as anti-cancer therapy.